Efektivitas Keroncong Garapan Orkes Keroncong Tresnawara terhadap Audiensi Generasi Muda - Nugrahanstya Cahya Widyanta (Universitas Gadjah Mada, 2017)
Nowadays, kroncong of music seems less attractive to young people. The listener of this style of music is dominated by the elders. Orkes kroncong Tresnawara appeared to revive kroncong to be more appealing to younger generation. Orkes kroncong Tresnawara modifi ed kroncong in its every performance to be fi twith the musical taste of the younger generation. Kroncong creation relatively has high tempo and dynamic beat with thebeat syncopation with accents. It brings orkes kroncong Tresnawara a unique musical style. The style andits young players make the kroncong song arranged by this group is very appealing to the youth. Kroncong creation is a mean chosen by orkes kroncong Tresnawara to communicate with young people. In this modern era, the environment and function are different. Therefore, Orkes kroncong Tresnawara attempts to adapt to the era